FACTORS INFLUENCING SUSTAINABILITY OF IRRIGATION PROJECTS IN MUKUNGULI MARSHLAND IRRIGATION SCHEME KAMONYI DISTRICT - Thierry, Mugabe (International Journal of Scientific Research and Management (IJSRM), 2022)
The study sought to establish the factors influencing sustainability of irrigation projects in Mukunguli marshland irrigation scheme in Kamonyi District. Mukunguli marshland irrigation scheme is very crucial economic activity for the provision of food to the inhabitant of the area, create employment, eradicate poverty and mitigate the problem of rural urban migration. The objective of the study sought to establish how water availability, technical, institutional and financial factors influence sustainability of irrigation projects in Mukunguli marshland irrigation scheme in Kamonyi. Survey design of the study was employed in the research. Sample size of 103 farmers both large scale and small scale was picked for interview based on where there are settled within the administrative units of Mukunguli marshland irrigation scheme in Kamonyi. Questionnaires were the data collection tools used. To establish the reliability of research instruments, test retest technique was used to test reliability of instruments. The study supervisor examined the content of the instruments and advised the researcher on its validity. For data analysis quantitative technique was employed using the statistical package for social sciences (SPSS) and results presented in tables that indicated percentages of a given attribute. The percentages were further analyzed to provide patterns and relationships from which conclusions were drawn. Linear regression model and Pearson‟s correlation analysis was done to analyze data. The result showed that water availability, Technology used in irrigation systems, institutional and financial factors had significant influence on success of irrigation projects in Mukunguli marshland irrigation scheme in Kamonyi. The study therefore recommended: National and County Government to put in place policies to ensure sustainable and efficient utilization of water resource for irrigation projects, Community based organizations to be assisted to get efficient and affordable spare parts, Training of management committees on operations and maintenance of irrigation systems, Management committees to be assisted in setting up tariffs for water consumption fees that would be used in repairs and maintenance of irrigation systems. Women should be encouraged to participate in this economic activity to boost standard of living of people in Kamonyi District.